2004
DOI: 10.1002/jms.729
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometric data–FAAH inhibitory activity relationships of some carbamic acid O‐aryl esters

Abstract: We have recently described a class of systemically active inhibitors of the intracellular activity of fatty acid amide hydrolase (FAAH) and traced extensive structure-activity relationships. These compounds, characterized by an N-alkyl carbamic acid O-aryl ester structure, exert potent anxiolytic-like effects in animal models. In the present study, possible relationships between mass spectrometric parameters (related to the propensity of the C(O) -O bond to be cleaved) and FAAH-inhibitory potency were tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
41
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 12 publications
4
41
0
Order By: Relevance
“…5 This supported the hypothesis that the ease of C(O)-O bond cleavage was relevant to explain FAAH inhibition. The results thus obtained justified the proposal of a binding mode to FAAH, 5,8,9 later supported by other authors, 13 alternative to that initially hypothesized.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…5 This supported the hypothesis that the ease of C(O)-O bond cleavage was relevant to explain FAAH inhibition. The results thus obtained justified the proposal of a binding mode to FAAH, 5,8,9 later supported by other authors, 13 alternative to that initially hypothesized.…”
supporting
confidence: 72%
“…5 This supported the hypothesis that the ease of C(O)-O bond cleavage was relevant to explain FAAH inhibition. The results thus obtained justified the proposal of a binding mode to FAAH, 5,8,9 later supported by other authors, 13 alternative to that initially hypothesized. 7 In the present investigation we applied the previously described approach to a series of biphenyl-3-yl carbamate analogs of URB524 (19, Table 1) with electron-withdrawing or electron-donating substituents on the distal (1-10, Table 1) 8 and proximal (11-18, Table 1) 9 phenyl rings.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…1), can be docked in two possible orientations (called orientations I and II) within the FAAH catalytic site. 6,7 Recently, hybrid quantum mechanical/molecular mechanics (QM/MM) modelling, 8 using the B3LYP/6-31G(d)//PM3-CHARMM22 potential, showed that the inhibitory process is energetically preferred in orientation II. 9 This orientation allows the catalytic nucleophile, Ser241, to efficiently attack the carbonyl group of URB524 (Fig.…”
mentioning
confidence: 99%